Pulmonary rehabilitation in multi-drug resistant tuberculosis (TB MDR): a case report (Colombia Medica, 2009)
Introduction: In tuberculosis (Tb), the great inflammatory component causes major injuries that trigger fibroblastic reaction, fibrosis and chest wall retraction, compromising pulmonary expansion, which translates into a clinically and functionally moderate restrictive pattern and dyspnea during exercise. This favors lung disability, causing economic and social dependence upon the nuclear family. Measures to control the Tb disease are merely focused on healing; and this fact must be considered insufficient because the actions aimed to habilitation and rehabilitation could prevent or reduce the incidence of Tb by cardiopulmonary disability. The importance of pulmonary rehabilitation (PR) as a nonpharmacological treatment in patients with chronic respiratory disease and/or risk factors for acquiring such is documented in the literature, and its application improves the physical condition of the patient and restores health-related quality of life (HRQOL), autonomy, and social integration. Objective: To describe the deterioration of the functionality of a patient with multi-drug resistant tuberculosis (MDR-TB) and that patient’s recovery in a PR program. Results: An increase of the distance covered in the six-minute walk test (6MWT) from 240 m to 350 m was observed. Dyspnea score with the medical research council (MRC) improved from 4 to 1, and improved from 7 to 0 with the Borg scale. The upper and lower limb muscle strength increased from 3 to 4. Conclusion: A period of PR of 8 to 10 weeks was enough to improve patient functionality.